Magnetic Properties of Nano-Iron Oxide α-Fe2O3 Prepared in Green Chemistry from Capsicum Plant Extract - Al-Redha, Hassan M.A.; Mahdi, Waleed K. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2026)
In this study, iron oxide nanoparticles (α-Fe₂O₃ NPs) were prepared using a readily available chili pepper plant extract from local markets. This study aims to evaluate the magnetic properties of α-Fe₂O₃ prepared in green chemistry from Capsicum plant extract. After several simple preparatory steps, such as washing and cutting, they were treated with an inorganic complex (potassium hexacyanoferrate) (K3[Fe(CN)₆]). In the first analytical step, the in vitro detection of the plant extract solution after reaction with the potassium hexacyanoferrate (III) complex revealed characteristic adsorption bands of the cyanide group, which disappeared upon complexation. The iron oxide NPs were characterized using various methods, including X-ray diffraction, energy-dispersive X-ray spectroscopy, scanning electron microscopy, transmission electron microscopy, and atomic force microscopy. The second step, testing the magnetic properties, was conducted using a vibrating sample magnetometer, which revealed strong magnetic properties. This novel method utilizes green chemistry to identify superparamagnetic properties.